2001
DOI: 10.1126/science.294.5543.870
|View full text |Cite
|
Sign up to set email alerts
|

The Plasticity of Dendritic Cell Responses to Pathogens and Their Components

Abstract: Dendritic cells are involved in the initiation of both innate and adaptive immunity. To systematically explore how dendritic cells modulate the immune system in response to different pathogens, we used oligonucleotide microarrays to measure gene expression profiles of dendritic cells in response to Escherichia coli, Candida albicans, and influenza virus as well as to their molecular components. Both a shared core response and pathogen-specific programs of gene expression were observed upon exposure to each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
515
2
9

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 691 publications
(569 citation statements)
references
References 30 publications
41
515
2
9
Order By: Relevance
“…In agreement with the human data (Perrier et al 18 and references therein; Huang et al 19 ), treatment with LPS had a profound effect on the transcriptional profile of the mouse DC. Additionally, the set of mouse genes modulated by LPS corresponds to those reported for human.…”
Section: Transcriptional Profile Of Lps-treated DCsupporting
confidence: 88%
“…In agreement with the human data (Perrier et al 18 and references therein; Huang et al 19 ), treatment with LPS had a profound effect on the transcriptional profile of the mouse DC. Additionally, the set of mouse genes modulated by LPS corresponds to those reported for human.…”
Section: Transcriptional Profile Of Lps-treated DCsupporting
confidence: 88%
“…The quantitative effects of lipid A on reprogramming dendritic cell gene expression are consistent with other studies examining the impact of TLR agonists and pathogens on the macrophage or dendritic cell transcriptome [21][22][23][24]. Importantly, the expression of 47.4% (n=200) of all genes that are regulated by lipid A in wild-type dendritic cells (n=421) was significantly changed by G 2-fold in cells of Trif Lps2/Lps2 mutant mice.…”
Section: Trif Is a Major Regulator Of Tlr4-stimulated Dendritic Cell supporting
confidence: 85%
“…Different TLR are reported to share a common signal transduction pathway similar to that of the interleukin-1 receptor [33]. However, it has been demonstrated that stimulation of TLR2, TLR3 or TLR4 induces separate sets of genes in some mammalian cell culture systems [34]. The latter finding is in agreement with the present study, demonstrating that a combined LPS and poly-I-C stimulation resulted in enhancement of bradykinin-induced contractions, much stronger than the ones obtained with each agonist separately.…”
Section: Discussionmentioning
confidence: 99%